Mutations in parkinsonian syndromes - Singleton, Andrew (Henry Stewart Talks, 2007)
Historic genetic research into PD, Previous difficulties in identifying genetic basis, Recent advances, Discovery of mutations in alpha-synuclein, parkin, DJ-1, PINK1 and LRRK2, Therapeutic directions
Archived at 2021/02/25